Spontaneous Imbibition and Forced Water Injection in Mixed-Wet Multiscale Oolitic Limestone Studied Through the Differential Imaging-Based Porous Plate Technique - Anindityo Patmonoaji; Asli S. Gundogar; Qianqian Ma; Mohamed Regaieg; Martin J. Blunt; Branko Bijeljic (Transport in Porous Media, 2025)
Understanding imbibition in multiscale porous carbonates is essential for predicting fluid distribution in subsurface applications. We measured the capillary pressure for spontaneous imbibition and forced water injection in a mixed-wet multiscale oolitic limestone with distinct macro-, intermediate-size-, and micropore structure using the differential imaging-based porous plate (DIPP) technique. Spontaneous imbibition was found to occur through water-wet micropore channels, whereas forced water injection was dominated by the flow in mixed-wet and oil-wet macro-pores with residual oil found in pores of intermediate size. The analysis of contact angle, curvature, macro-pore occupancy, and overall water Amott index demonstrated mixed-wet-to-oil-wet conditions, resulting in a percolation-like advance during forced water injection. The water Amott index calculated on each pore size classification indicated water-wet micropores and oil-wet intermediate-size- and macro-pores. Our results highlight the role of micropores in sustaining water flow at low saturation and the role of intermediate-size-pores in retaining residual oil, advancing the predictive understanding of fluid behavior in carbonate reservoirs.